"Workshop. Human rights – contemporary threats and challenges” : sprawozdanie z międzynarodowej konferencji naukowej, Wrocław 2016 - Kuriata, Agnieszka (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
On May 30–31, 2016, an international academic conference “Workshop: Human Rights – Contemporary Threats and Challenges” took place at the Faculty of Law, Administration and Economics of the University of Wroclaw. The participants included representatives of many research centers from both Poland (Jagiellonian University and the University of Lodz, among others) and abroad (the University of Manchester, the University of Oslo, and Victoria University of Wellington). During the conference the participants presented their research on broadly-understood human rights and their functioning in the contemporary world
Keywords: reports; human rights; international conference; oriental laws research